Care of the State Relationships, Kinship and the State in Children$1 (Bs Homes in Late Socialist Hungary /s - Rasell, Jennifer; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2020)
Care of the State blends archival, oral history, interview and ethnographic data to study the changing relationships and kinship ties of children who lived in state residential care in socialist Hungary. It advances anthropological understanding of kinship and the workings of the state by exploring how various state actors and practices shaped kin ties. Jennifer Rasell shows that norms and processes in the Hungarian welfare system placed symbolic weight on nuclear families whilst restricting and devaluing other possible ties for children in care, in particular to siblings, friends, welfare workers and wider communities. In focussing on care practices both within and outside kin relations, Rasell shows that children valued relationships that were produced through personal attention, engagement and emotional connections. Highlighting the diversity of experiences in state care in socialist Hungary, this book$1 (Bs nuanced insights represent an important contribution to research on children$1 (Bs well-being and family policies in Central-Eastern Europe and beyond.s
1. Care as a Frame for Understanding the Mutual Constitution of State and Kinship -- 2. Not a Fading Problem: Child Protection from the 1950s to the 1980s -- 3. Negotiating Care Between Parents and State Officials -- 4. The Continuing Family Relations of Children in Care -- 5. Care in the Children$1 (Bs Home and Wider Circles of Belonging -- 6. Conclusions: The Processes of Producing Kinship and the State in Residential Care.s
Keywords: Ethnology; Social groups; Family; Political sociology; Russia$1 (BHistory.s; Europe, Eastern$1 (BHistory.s; Social Anthropology; Sociology of Family, Youth and Aging; Political Sociology; Russian, Soviet, and East European History